Pós-modernidade e catolicismo na América Latina e no Caribe : posicionamentos pastorais de Aparecida diante dos principais desafios da cultura contemporânea - V CELAM - V Conferência Geral do Episcopado Latino-Americano e do Caribe 13-31 de maio de 2007 - Barros, Maria José Cavalcante (2008)
How to characterize the contemporary culture? What is the key for understanding the post modern human being? The work rescues, through wide flicks, the genealogical line of the contemporary culture, called Post-Modernity, with its complexity, presenting themselves paradoxically as rupture and continuity with that one. Through a historical and critical analysis, making use of the interdisciplinary dialogical interaction, it picks and detaches the main characteristic traces of this culture and of this citizen, offering keys of bigger understanding of its expressions of rupture and continuity with the previous paradigm. In this context, it is placed the Catholic Church, who, interpellated by it, detects the main challenges and possibilities and searches, in the ways of auto-understanding the dialogue with this culture and this citizen. Vatican Council II was this door of access, offered this key of reading, reread and continued - for Latin America and the Caribbean - through the four Episcopal Conferences that came after the Council. The research covers this itinerary and looks - with closer lenses - in the V General Conference of the Episcopate, in Aparecida, in 2007, for the main orientations that show themselves in the catholic guidances of the Latin American and Caribbean continent, in the process of aggiornamento initiated by the Council mentioned before.